2020
DOI: 10.1007/s10552-020-01379-w
|View full text |Cite
|
Sign up to set email alerts
|

Mammographic density as an image-based biomarker of therapy response in neoadjuvant-treated breast cancer patients

Abstract: Purpose Personalized cancer treatment requires predictive biomarkers, including image-based biomarkers. Breast cancer (BC) patients receiving neoadjuvant chemotherapy (NACT) are in a clinically vulnerable situation with the tumor present. This study investigated whether mammographic density (MD), assessed pre-NACT, is predictive of pathological complete response (pCR). Methods A total of 495 BC patients receiving NACT in Sweden 2005–2019 were included, mer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 28 publications
1
12
0
Order By: Relevance
“…Previously, the same group performed a retrospective study of 302 patients and concluded that women with BI-RADS d MD were less likely to achieve pCR post-NACT after adjusting for age and pre-treatment tumour characteristics. The results of both study sets were recently collated [ 14 ] and demonstrated that pre-menopausal women with category MD d were less likely to achieve pCR after NACT [ 14 ]. Conversely, a recent study of 442 patients by Di Cosimo et al concluded that those with denser breasts showed an increased likelihood of pCR with odds ratio (OR) of 1.70, 2.79 and 1.47 for b , c and d categories.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, the same group performed a retrospective study of 302 patients and concluded that women with BI-RADS d MD were less likely to achieve pCR post-NACT after adjusting for age and pre-treatment tumour characteristics. The results of both study sets were recently collated [ 14 ] and demonstrated that pre-menopausal women with category MD d were less likely to achieve pCR after NACT [ 14 ]. Conversely, a recent study of 442 patients by Di Cosimo et al concluded that those with denser breasts showed an increased likelihood of pCR with odds ratio (OR) of 1.70, 2.79 and 1.47 for b , c and d categories.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Swedish researchers analyzed the association between pCR after NCT and MD using visual assessment with BI-RADS in 495 patients with breast cancer [ 12 ]. In a model adjusted for patient age, BMI, and menopausal status, the pCR rates were significantly lower in premenopausal women classified as BI-RADS D, which represents extremely dense breasts [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Swedish researchers analyzed the association between pCR after NCT and MD using visual assessment with BI-RADS in 495 patients with breast cancer [ 12 ]. In a model adjusted for patient age, BMI, and menopausal status, the pCR rates were significantly lower in premenopausal women classified as BI-RADS D, which represents extremely dense breasts [ 12 ]. Consistently, our multivariable analysis confirmed that higher Qabd categories and decreased ΔVbd% were significantly independently associated with lower pCR rates, whereas aggressive breast cancer subtype, high-grade tumor, and use of anti-HER2 agents with chemotherapy were significantly associated with increased pCR rates after NCT.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1. The study cohort (453 patients) consisted of a retrospective (N = 258, treatment period 2005-2016) and a prospective cohort (N = 195, treatment period 2014-2019) as previously described [18]. The inclusion criteria for both cohorts were female patients treated with NACT undergoing the intended breast surgery.…”
Section: Cohortmentioning
confidence: 99%